Effect of angular speed variations on the nonlinear vibrations of a rotational spring-mass system - Pakdemirli, Mehmet (Zielona Góra: Uniwersytet Zielonogórski)
A rotating spring-mass system is considered using polar coordinates. The system contains a cubic nonlinear spring with damping. The angular velocity harmonically fluctuates about a mean velocity. The dimensionless equations of motion are derived first. The velocity fluctuations resulted in a direct and parametric forcing terms. Approximate analytical solutions are sought using the Method of Multiple Scales, a perturbation technique.
Keywords: spring-mass system; nonlinear rotational vibrations; velocity fluctuations; resonance; method of multiple scales